Fiume 1868-1918: Erisz almája, avagy lebegő gyöngyszem Szent István koronáján? - Hajdú, Zoltán (Közép-Európai Közlemények, 2013)
The Hungarian-Croatian Compromise was regulated by the article XXX of 1868, reached between the Parlament of Hungarian Kingdom on the one hand and the Sabor of Croatia, Slavonia and Dalmatia on the other hand. The article XXX of 1868 turned to be a joint basic law of Hungary and of Croatia, Slavonia and Dalmatia. Hungary and Croatia, Slavonia and Dalmatia form one state unity, alike towards to the other territories under His Majesty’s rule and towards other countries. Fiume, the only important harbour of Hungary and district of Fiume form a “separatum sacrae regni coronae adnexum corpus”, with regard to whose special autonomy and the legislative and administrative conditions. A new aggreement is to be reached by means of negotiations between the Hungarian Parliament, the Sabor of Croatia, Slavonia and Dalmatia and the town of Fiume for a joint understanding.